Minor H antigen matches and mismatches are equally distributed among recipients with or without complications after HLA identical sibling renal transplantation. Issue 5 (4th October 2013) - Dierselhuis, M. P.; Spierings, E.; Drabbels, J.; Hendriks, M.; Alaez, C.; Alberú, J.; Alvarez, M. B.; Burlingham, W.; Campos, E.; Christiaans, M.; Claas, F.; Fasano, M. E.; et al.
Abstract Studies of the effect of minor H antigen mismatching on the outcome of renal transplantation are scarce and concern mainly single center studies. The International Histocompatibility and Immunogenetics Workshops (IHIW) provide a collaborative platform to execute crucial large studies. In collaboration with 16 laboratories of the IHIW, the role of 15 autosomal, 10 Y‐chromosome encoded minor H antigens and 3 CD31 polymorphisms, was investigated in relation to the incidence of renal graft rejection and graft loss in 444 human leukocyte antigens (HLA)‐identical sibling renal transplantations. Recipient and donor DNA samples were genotyped for the minor H antigens HA‐1, HA‐2, HA‐3, HA‐8, HB‐1, ACC‐1, ACC‐2, SP110, PANE1, UGT2B17, C19Orf48, LB‐ECGF‐1, CTSH, LRH‐1, LB‐ADIR and HY. The correlation between minor H antigen mismatch and the primary outcome graft rejection or graft loss was statistically analyzed. The incidence of rejection was very low and no correlation was observed between one or more minor H antigen mismatch(es) and a rejection episode (n = 36), of which only eight resulted in graft loss. In summary, in our study cohort of 444 renal transplants, mismatching for neither autosomal nor HY minor H antigens correlate with rejection episodes or with graft loss.